HUBUNGAN ANTARA KEMAMPUAN BERSENAM DENGAN KEMAMPUAN MENARI PADA ANAK USIA DINI KELOMPOK USIA 5-6 TAHUN TK AISYIYAH BUSTANUL ATHFAL 57 SURABAYA - Ahmad Fachrurrazi (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to determine the relationship between the ability to exercise with the ability to dance in early childhood group b aged 5-6 years TK Aisyiyah Bustanul Athfal 57 Surabaya. Ability is a potential for a person or individual to master expertise in doing or doing various tasks in a job or an assessment of someone's actions. Gymnastics is an activity that can stimulate physical-motor development in early childhood. Through gymnastics activities, it is hoped that other abilities or intelligences can also develop properly and can make children who are healthy, smart, cheerful and have character. Meanwhile, dancing is a feeling conveyed through beautiful rhythmic movements. This study uses a quantitative approach with a correlation research design with Product Moment correlation. Data were collected using participatory observation techniques. The results of data analysis show that the value of rcount is 0.973. While the rtable index was 0.4227 for the 0.05 significance level, and 0.5368 for the 0.01 significance level with N = 20. Thus hypothesis 0 (h0) is rejected so that the working hypothesis (h1) is accepted. The r-count value = 0.973 is in the range of 0.800 to 1.00, including in the high correlation category between variable x and variable y.It can be concluded that there is a relationship between the ability to exercise and the ability to dance in early childhood group B aged 5-6 years at TK Aisyiyah Bustanul Athfal 57 Surabaya. The relationship between the two variables is a symmetrical relationship, meaning that if one variable increases, the other variable also increases. Thus it can be said that there is a strong relationship between the ability of gymnastics to dance. This may imply that the better the child's exercise skills, the better the ability to dance.